Ecclesiastes - Miller, Douglas B., 1955- (Scottdale, Pa. : Herald Press, 2010)
In this 23rd volume of the Believers Church Bible Commentary Series, Doug Miller respects the pastoral and theological contribution of Ecclesiastes, without muting its critique of simplistic and comfortable approaches to the life of faith. --From publisher's description.
Introduction to Ecclesiastes -- Introduction to Qohelet (1:1) -- PART 1 (1:2-6:9) : Human effort. All is vapor (1:2-11) -- The king's experiment (1:12-2:26) -- God's work in time and eternity (3:1-22) -- Toil for self and in community (4:1-16) -- Words before God (5:1-7) -- Enjoyment instead of greed (5:8-6:9) -- -- PART 2 (6:10-12:8) : Human limits. No one knows what is good (6:10-7:14) -- Wisdom and righteousness (7:15-29) -- Even the wise do not know (8:1-17) -- Enjoy life now (9:1-10) -- Time and chance (9:11-10:15) -- Living with risks (10:16-11:6) -- Youth and old age (11:7-12:8) -- Epilogue (12:9-14).
Includes bibliographical references (p. 273-282) and index.
Description based on print version record.
Keywords: Bible. -- Commentaries; RELIGION / Biblical Studies / Old Testament; RELIGION / Biblical Studies / Wisdom Literature; Electronic books